2012
DOI: 10.1016/j.jana.2011.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Providing Effective Medical and Case Management Services to HIV-Infected Youth Preparing to Transition to Adult Care

Abstract: A key aspect of maintaining health for HIV-infected adolescents is the transition from pediatric care to adult medical care. Because young people who were infected with HIV as children were initially not expected to survive until adulthood, relatively little attention has been given to issues associated with this transition to adult care. With improved life expectancies, health professionals are increasingly faced with the new challenge of working with these young people as they grapple with the unique experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…This description of YALHA is consistent with findings of other HIV studies in Uganda and sub-Saharan Africa, which have shown that HIV is most prevalent among women living in urban areas 25,26. Similarly, one study has shown that young adults living with HIV are sexually active and do not disclose their HIV status among their peers 27. However, it is important to note that females in general also tend to have better health-seeking behaviors and this could be one of the reasons to explain their large number in the sample for the current study.…”
Section: Discussionsupporting
confidence: 89%
“…This description of YALHA is consistent with findings of other HIV studies in Uganda and sub-Saharan Africa, which have shown that HIV is most prevalent among women living in urban areas 25,26. Similarly, one study has shown that young adults living with HIV are sexually active and do not disclose their HIV status among their peers 27. However, it is important to note that females in general also tend to have better health-seeking behaviors and this could be one of the reasons to explain their large number in the sample for the current study.…”
Section: Discussionsupporting
confidence: 89%
“…Other studies have consistently shown the importance of dedicated health and social workers to support transition in the United States [5153], and having trusting relationships with health providers [25, 30], which may often require additional training to improve competency of health providers [30] to enable them to receive adolescents and create atmosphere which enables communication and questions from adolescents. Creating familiarity with adult clinics, including through visits has a significant impact in facilitating adolescents’ connection to the adult clinic consistent with research from other settings [33].…”
Section: Discussionmentioning
confidence: 99%
“…These difficulties are not surprising. The issue of transition has unexpectedly been brought to fore due to increasing survival of perinatally-infected children, against a prior assumption that they would not survive into adulthood [30]. Although studies looking at survival of adolescents after transition have emerged prompted by the rising numbers of this population, most focus on experiences, retention and retrospective clinical outcomes in developed countries [27, 3134], leaving a gap of information related to transition processes in low and middle income countries.…”
Section: Introductionmentioning
confidence: 99%
“…4 ,12 ,and 18 in this volume). Moreover, infected youth are twice as likely to be prescribed psychotropic medications than their uninfected peers (as cited in Boudreau and Fisher 2012 ). Unsurprisingly, they are more likely to experience psychiatric illness, substance abuse, and other high risk behaviors, all of which may have adverse health effects .…”
Section: Developmental Functioning and Mental Healthmentioning
confidence: 99%
“…Our ill-preparedness is thought to be, at least in part, due to the reality that HIV-infected children were, in the not so distant past, not expected to survive into adulthood Boudreau and Fisher 2012 ). Our ill-preparedness is thought to be, at least in part, due to the reality that HIV-infected children were, in the not so distant past, not expected to survive into adulthood Boudreau and Fisher 2012 ).…”
Section: Introductionmentioning
confidence: 99%